1997
DOI: 10.1172/jci119432
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms permitting nephrotic patients to achieve nitrogen equilibrium with a protein-restricted diet.

Abstract: Clinical experience suggests nephrotic patients are at risk for malnutrition. To determine if nephrotic patients can adapt successfully to a protein-restricted diet, nephrotic (glomerular filtration rate, 52 Ϯ 15 ml/min; urinary protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 40 publications
0
36
0
4
Order By: Relevance
“…If there has been loss of muscle mass but no reason that protein breakdown is accelerated by other illnesses, then 0.8 g/kg per d of dietary protein will be sufficient (20). With proteinuria, the diet should contain no more than 0.8 g of protein/kg per d plus 1 g of protein per gram of proteinuria; even less dietary protein may be sufficient (20,22).…”
mentioning
confidence: 99%
“…If there has been loss of muscle mass but no reason that protein breakdown is accelerated by other illnesses, then 0.8 g/kg per d of dietary protein will be sufficient (20). With proteinuria, the diet should contain no more than 0.8 g of protein/kg per d plus 1 g of protein per gram of proteinuria; even less dietary protein may be sufficient (20,22).…”
mentioning
confidence: 99%
“…Intestinal edema developing secondary to massive proteinuria-associated hypoalbuminemia reduces nutrient absorption and leads to malnutrition and activation of inflammatory cascade. Various inflammatory mediators (such as TNF α) exhibit a negative inotropic effect on the myocardium (5,18,19). In this way, malnutrition and inflammation lead to an increase in cardiovascular events incidence in the NS patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria in NS patients causes inflammatory cytokine release during endothelial injury, tubular reabsorption and tubular catabolism (23,24). In addition, malnutrition developing secondary to hypoalbuminemia leads to inflammatory cascade activation and cytokine release (5,18,19). Studies have shown that inflammatory cytokines cause myocardial injury (5).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian Maroni BJ dkk 16 terhadap 5 pasien sindrom nefrotik dewasa yang mendapatkan diet rendah protein dan tinggi protein ternyata didapatkan keseimbangan nitrogen yang positif baik pada kelompok rendah maupun tinggi protein. Pada penelitian ini protein diberikan mulai dari 1,5 g/kgBB/ hari dan terbukti meningkatkan kadar protein dan albumin serum.…”
Section: Pembahasanunclassified
“…[19][20] Salah satu pengukuran untuk menilai penggunaan protein diet adalah dengan keseimbangan nitrogen. [15][16] Penelitian untuk mengetahui kinerja protein dari diet dengan menggunakan teknik N labeled protein didapatkan bahwa nitrogen diet lebih berperan pada jalur anabolisme yaitu sintesis protein. 21 Patogenesis sintesis protein pada sindrom nefrotik adalah multifaktorial dan dipengaruhi juga oleh kadar proteinuria.…”
Section: Pembahasanunclassified